Get a life - Gordimer, Nadine 1923-2014 (Farrar, Straus, Giroux, 2005)
Paul Bannerman, an ecologist living in South Africa, begins to re-examine his life after he is diagnosed with thyroid cancer and begins radiation treatments--an isolating experience that forces him to confront his relationships with family and friends.